(untitled) (International Journal of Current Engineering and Technology, 2015)
A hybrid cloud is a combination of public and private clouds bound together by either standardized or proprietary technology that enables data and application portability. Proposed system aiming to efficiently solving the problem of deduplication with differential privileges in cloud computing. A hybrid cloud architecture consisting of a public cloud and a private cloud and the data owners only outsource their data storage by utilizing public cloud while the data operation is managed in private cloud. To make data management scalable in cloud computing, deduplication has been a very well-known technique recently is use. Deduplication reduces your bandwidth requirements, speeds up the data transfers, and it keeps your cloud storage needs to a minimum. Proposed system present several new deduplication constructions supporting authorized duplicate check in hybrid cloud architecture. To maintain the confidentiality of data the convergent encryption technique has been used to encrypt the data before outsourcing. Authorized deduplication system support differential authorization duplicate check. As a proof of concept, a prototype is implemented in authorized duplicate check scheme and conduct test bed experiments using prototype, authorized duplicate check scheme incurs minimal overhead compared to normal operations.